Identification and deployment of QTL for Fusarium head blight resistance in U.S. hard winter wheat - Fatima, Nosheen (Kansas State University, 2016)
Fusarium head blight (FHB) is one of the most damaging diseases in wheat, which impacts both grain yield and quality drastically. Recently, the disease has become more prevalent in the hard winter wheat (HWW) grown areas of the United States including Oklahoma where FHB has not been reported before. Growing resistant cultivars is the most economical and effective strategy for disease management. To dissect quantitative trait loci (QTL) for FHB resistance in a moderately resistant hard winter wheat (HWW) cultivar, Overland, a population of 186 recombinant inbred lines (RILs) was developed from the cross between Overland and Overley, a susceptible HWW cultivar from Kansas. The RILs were evaluated for FHB type II resistance in one field and three greenhouse experiments and genotyped using genotyping-by-sequencing (GBS) markers. Three FHB resistance QTLs were mapped on Chromosomes 4DL, 4AL, and 5BL. The QTL on 4DL was the most consistent one and explained up to 13% of the phenotypic variation for type II resistance and 14 % for low Fusarium damaged kernels (FDK). Two GBS markers closely linked to the 4DL QTL were successfully converted to Kbioscience competitive allelic specific PCR (KASP) assays and can be used in marker-assisted breeding. In breeding, a single QTL may provide only partial resistance and pyramiding of several resistance QTLs in a cultivar can provide more protection in FHB epidemics. Fhb1 is a major QTL for FHB resistance from a Chinese source and Fhb3 is an alien gene from wild rye grass (Leymus racemosus). To study the effects of these QTLs individually and cumulatively in hard winter wheat backgrounds, they were transferred into two HWW cultivars Overland and Jagger. The results show that Fhb1 significantly increased FHB resistance, but Fhb3 did not. Thus, Fhb3 is not an effective gene for improvement of FHB resistance in HWW.
Keywords: QTL mapping in U.S. winter wheat